1998
DOI: 10.1007/s001980050096
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Efficacy of Hormone Replacement Therapy in the Prevention of Hip Fracture

Abstract: Use of postmenopausal hormone replacement therapy (HRT) has been associated with a reduced risk of osteoporotic fractures. However, it is uncertain whether this risk reduction is modified by other risk factors for hip fracture. In a population-based case-control study in Sweden, we investigated the association between HRT and hip fracture risk within categories of age, body measures and lifestyle factors in postmenopausal women, 50-81 years of age. Mailed questionnaires and telephone interviews were used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 41 publications
(34 reference statements)
1
16
0
1
Order By: Relevance
“…It is also a limitation of the present study that hormone replacement therapy (HRT) was not accounted for in our study as an osteoporosis medication because of the pleiotropic actions of substitution therapy in elderly women. Although HRT is no longer considered as a first-line treatment for osteoporosis, in postmenopausal women without climacteric symptoms, it is well recognized that HRT has a protective effect on fracture risk (36), with variation in the efficacy according to risk factors (37,38). One cannot rule out that part of the reduction in fracture incidence observed in women is related to the widespread use of estrogens, particularly before the publication of the Women's Health Initiative study.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a limitation of the present study that hormone replacement therapy (HRT) was not accounted for in our study as an osteoporosis medication because of the pleiotropic actions of substitution therapy in elderly women. Although HRT is no longer considered as a first-line treatment for osteoporosis, in postmenopausal women without climacteric symptoms, it is well recognized that HRT has a protective effect on fracture risk (36), with variation in the efficacy according to risk factors (37,38). One cannot rule out that part of the reduction in fracture incidence observed in women is related to the widespread use of estrogens, particularly before the publication of the Women's Health Initiative study.…”
Section: Discussionmentioning
confidence: 99%
“…However, baseline values (such as the presence of fractures prior to therapy in some subjects) make these data difficult to interpret in at least one of these studies [26]. Bjarnason and Christiansen [27] found that BMI did not influence the response to HRT treatment, whereas a large study evaluating postmenopausal risk factors for hip fracture found that the best protective effect of HRT was among leaner women [28]. Our BMC results using a wider range of body weights are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies also support these studies in that reductions in fracture risk that are obtained with HT are lost after discontinuation of therapy. In some studies, women who discontinued therapy had rates of fracture and bone loss similar to those who had never taken HT (54,55).…”
Section: Discontinuation Of Estrogen Therapymentioning
confidence: 99%